MATHEMATICAL MODEL OF TRANSIENT PROCESSES PERTAIN-ING TO THREE-IMPULSE SYSTEM FOR AUTOMATIC CONTROL OF STEAM GENERATOR WATER SUPPLY ON LOAD RELIEF - G. T. Kulakov; A. T. Kulakov; A. N. Kukharenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper analyzes an operation of the standard three-impulse automatic control system (ACS) for steam generator water supply. Mathematical model for checking its operational ability on load relief has been developed in the paper and this model makes it possible to determine maximum deviations of water level without execution of actual tests and any corrections in the plants for starting-up of technological protection  systems in accordance with water level in the drum.  The paper reveals reasons of static regulation errors while solving problems of internal and external distortions caused by expenditure of over-heated steam in the standard automatic control system. An actual significance of modernization pertaining to automatic control system for steam generator water supply has been substantiated in the paper.